CURRENT MEGATRENDS OF THE SOCIO-ECONOMIC DEVELOPMENT OF UKRAINE - IVANIUK, Uliana; KRAVCHENKO, Mariia (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article describes the main modern socio-economic megatrends in Ukraine. It has been proven that the level of resilience of the socio-economic system not only in Ukraine has significantly decreased as a result of the disruption of the logistics channels for the supply of food and agricultural products, as well as the properties of stability and adaptability of the economic systems of most countries of the world with low and medium income levels have been significantly disturbed, as the cost has increased significantly of essential products (food), which affects both the solvency and the level of consumption in GDP. In the context of the acquisition of a high level of resilience in the socio-economic system, studying its diversification and export orientation requires special attention. This is important in the conditions of the low level of solvency of domestic consumers, which does not contribute to the development of the domestic market, the reduction of trade turnover with foreign countries, the low effectiveness of stimulating domestic production, the high cost of technologies for Ukrainian manufacturers, which reduces the competitiveness of manufactured goods on the domestic and foreign markets, etc. The following are possible environmental threats that are the consequences of the Russian Federation’s invasion of Ukraine. The risk of the resilience of socio-economic systems due to the growth of migration processes, particularly the increase in the number of internally displaced persons (IDPs), is outlined. Irreversible human losses due to hostilities and significant volumes of mass internal and external migration became the heaviest price for Ukraine. The military conflict leads to the loss of human potential as an essential endogenous factor in the resilience of the socio-economic system; namely, it occurs.